2020
DOI: 10.1002/cam4.3201
|View full text |Cite
|
Sign up to set email alerts
|

Switches of SOX17 and SOX2 expression in the development of squamous metaplasia and squamous intraepithelial lesions of the uterine cervix

Abstract: Aims The dynamics and topographical distribution of SOX17 and SOX2 expression was studied in the transformation zone (TZ) of the uterine cervix. This TZ is a dynamic area where switches from glandular into squamous epithelium can be recognized, new squamocolumnar junctions are formed, and premalignant lesions originate. SOX17 and SOX2 show mutually exclusive expression patterns in the normal uterine cervix, with SOX2 being exclusively found in squamous epithelium, while SOX17 is detected in endocervical column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…In contrast to the infrequent observations of squamous Intern Med Advance Publication DOI: 10.2169/internalmedicine.6271-20 metaplasia in the stomach, transition of the epithelium to squamous cells is more commonly seen in the uterine cervix, bladder, and airways (5). Such squamous metaplasia is considered to develop as a consequence of mechanical irritation and/or chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the infrequent observations of squamous Intern Med Advance Publication DOI: 10.2169/internalmedicine.6271-20 metaplasia in the stomach, transition of the epithelium to squamous cells is more commonly seen in the uterine cervix, bladder, and airways (5). Such squamous metaplasia is considered to develop as a consequence of mechanical irritation and/or chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that SOX2 was related to HPV infection. Interestingly, HPV infection drives switches in SOX2 expression in the transformation zone in the uterine cervix [ 15 ], and SOX2 locus amplification was related with HPV mRNA positivity in vulvar carcinoma [ 14 ]. Furthermore, SOX2 was reported to be regulator of HPV16 at the transcriptional level in cervical squamous cell carcinoma [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The small infiltrating cancer nests surrounding CIN 3 margins or the CIN 3-like SCC with deep invasion generally display a decreased SOX2 level locally, and this indicates reduced SOX2 expression during invasive growth [ 13 ]. SOX2 has been reported to be related to HPV infection in previous studies [ 14 , 15 ]. However, its expression, clinical significance and the association between SOX2 and HPV status in SCNEC have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the inclusion criteria, 17 articles with 1906 participants (1172 cervical cancer patients and 734 control samples) were published between 2010 and 2020. 8,[11][12][13][14][15][20][21][22][23][24][25][26][27][28][29][30] These studies were conducted in China (n = 13), Korea (n = 1), Australia (n = 2), and The Netherlands (n = 1). Of these studies, seven studies evaluated the difference of SOX2 expression between cancer and CIN.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…7 Recently, some studies have reported the association between SOX2 expression and cervical cancer. [11][12][13] However, the clinical and prognostic significance of SOX2 in cervical cancer remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%